Evaluation of Crossover Number, Distribution, and Interference Using Cytological Assays in Arabidopsis. Issue 12 (5th December 2022) - Huang, Jiyue; Li, Xiang; Wang, Cong; Wang, Yingxiang
Abstract: Meiosis involves the replication of nuclear chromosomes in a parent cell, followed by two successive nuclear divisions to produce haploid spores, which differentiate into the gametophyte generations that produce the egg and sperm in plants. Meiotic recombination or crossover (CO) is a hallmark of meiosis that allows shuffling of genetic information between homologous chromosomes (homologs), thereby giving rise to genetically diverse progeny cells and, ultimately, individuals in the progeny; this opens vast opportunities for genetic differentiation and hence speciation. Meiotic COs also ensure the formation of bivalents and fidelity of their equal segregation. Therefore, mechanisms that regulate meiotic recombination have been extensively studied in multiple species. Several approaches have been developed to observe or estimate the frequency of CO, in which CO can be visualized and analyzed cytologically by estimating the number of chiasma (plural chiasmata), a position where non‐sister chromatids exchange genetic material between homologs. Furthermore, one CO event might influence the occurrence of another one nearby, along a chromosome; this is known as CO interference. Over the past decades, visualizing CO events and measuring CO interference have contributed greatly to our understanding of the regulatory mechanisms of meiotic recombination. Here, we describe protocols to estimate the number of chiasmata and CO interference in Arabidopsis using cytological methods involving chromosome spreads and immunostaining. Specifically, we describe how chromosome spreads can be used to estimate the number of chiasmata based on the conformations of metaphase I bivalents and provide a revised acid‐based quick immunostaining assay that permits high‐throughput and quantitative digital estimation of the relative distance between adjacent interference‐sensitive CO foci at diakinesis. These methods can be easily established or modified, if necessary, for studying meiotic recombination in other plants and crops. © 2022 Wiley Periodicals LLC. Basic Protocol 1 : Estimation of the number of chiasmata per nucleus based on metaphase I bivalent conformations Basic Protocol 2 : A chromosome spread–based immunostaining method for relative distance analysis of adjacent interference‐sensitive CO foci at diakinesis in Arabidopsis meiocytes